2021
DOI: 10.1007/s00405-021-06687-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation study of a novel approach for assessment of retronasal olfactory function with combination of odor thresholds and identification

Abstract: Purpose The present study aimed to establish a test battery for the clinical assessment of retronasal odor thresholds and retronasal odor identification. Study design Prospective case–control series. Methods Sixty participants (36 women, 24 men, mean age 37.6 ± 19.4 years) were enrolled in this study; 36 were healthy controls and 24 were patients with olfactory dysfunction. Orthonasal olfactory function was assessed with the “Sniffin’ Sticks”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Indeed, it has been shown that some physiological factors related to gustatory function, such as salivation, enzymes, chewing…, could influence retronasal stimulation. 58 The straw technique used in the present work, and in recent studies, 18,46,47 is another technique of retronasal stimulation in which no simultaneous gustatory stimulation occurs. This technique is non-invasive and allows a more ecological stimulation insofar as retronasal stimulation occurs during food intake, i.e., volatile molecules reach the olfactory epithelium via rhino-pharyngeal crossroad.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, it has been shown that some physiological factors related to gustatory function, such as salivation, enzymes, chewing…, could influence retronasal stimulation. 58 The straw technique used in the present work, and in recent studies, 18,46,47 is another technique of retronasal stimulation in which no simultaneous gustatory stimulation occurs. This technique is non-invasive and allows a more ecological stimulation insofar as retronasal stimulation occurs during food intake, i.e., volatile molecules reach the olfactory epithelium via rhino-pharyngeal crossroad.…”
Section: Discussionmentioning
confidence: 92%
“…The retronasal stimulation was based on the “straw” technique developed by Chen and Halpern 46 and used in recent studies 18,47 . Six millitres of each odorant were placed in a 30 mL amber glass bottle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This possible unequal affection of the ortho- and retronasal mucosa could be tested in studies using biopsies or brushings from the anterior and posterior part of the olfactory mucosa. Other possibilities would be the study of ortho- or retronasal odor thresholds [ 27 ] for parosmigenic odors [ 28 ].…”
Section: Discussionmentioning
confidence: 99%